Efektifitas Aloe vera terhadap Luka Bakar - Ashilah Mumtaz Hakim (Universitas Wijaya Kusuma Surabaya, 2020)
Herbal medicines are a form of treatment that is based on the use of plants with high bioactivity potential. These therapies have been used throughout history for the treatment of various diseases. Therapy has been passed down from generation to generation to become general knowledge related to culture, health, and improvement of quality of life for certain diseases. Aloe vera or Aloe vera is a cactus-like plant which, in several studies in experimental animals and humans, has been shown to have benefits. Used to accelerate wound healing, through complex biological processes that are responsible for tissue recovery and have been used since ancient times. Scientific evidence about the benefits of Aloe vera will be very useful, because its use can improve adherence to treatment of patients because the wound is rapidly improving and can also reduce costs. Aloe vera has been used externally to treat various skin conditions such as burns and eczema. Allegedly the sap from Aloe vera alleviates pain and reduces inflammation. Has antiseptic and antibiotic properties. Clinical studies based on scientific evidence are needed to get a better understanding of Aloe vera, its compounds and therapeutic indications).